Assessment of the Serum Levels of Nitric Oxide Among Diabetic Patients and its Correlation with Lipid Profile as Well as Oxidative Stress (Academia Journal of Medicine, 2020)
Background: Diabetes mellitus is a disease with a rapidly increasing prevalence needing continue research for novel methods to both prevent and treat this disorder. The present study was conducted to assess the serum levels of Nitric Oxide (NO) among diabetic patients and its correlation with lipid profile as well as oxidative stress. Subjects & Methods: 120 patients with diabetes were divided into three groups: Group I typed 2 diabetics with dyslipidemia and hyperuricaemia, group II have typed 2 diabetics with dyslipidemia and normouricaemia and group III was type 2 diabetics with normolipidemic and normouricaemia. A thorough clinical assessment was performed. Lipid profile and nitric oxide were determined. Results: Age group 20-40 years had 10 in group I, 15 in group II and 10 in group III, 40-60 years had 15 in group I, 13 in group II and 20 in group III and age group >60 years had 15in group I, 12 in group II and 10 in group III. There were 25 males and 15 females in group I, 22 males and 18 females in group II and 20 males and 20 females in group II. BMI (Kg/m2) was 18.5- 24.9 seen 2 in group I, 4 in group II and 6 in group III, 25- 29.9 seen 14 in group I, 12 in group II and 22 in group III, 30-34.9 seen 8 in group I, 20 in group II and 10 in group III and >35 seen 16 in group I, 4 in group II and 2 in group III. There was a non-significant difference in HbA1c, TC, TG, HDL and LDL among different differences (P> 0.05). Conclusion: There was a role of Nitric Oxide (NO) in the pathogenesis of type -2 diabetes mellitus with dyslipidemia and hyperuricaemia.
Keywords: Diabetes Mellitus; Hyperuricaemia; Nitric Oxide